A highly polymorphic caprine keratin-associated protein gene identified and its effect on cashmere traits. (9th August 2021) - Li, Shaobin; Xi, Qiming; Zhao, Fangfang; Wang, Jiqing; He, Zhaohua; Hu, Jiang; Liu, Xiu; Luo, Yuzhu
Abstract: Five keratin-associated protein 6 genes ( KRTAP6 ) have been identified in sheep and variation in some KRTAP6 has been associated with wool fiber diameter-related traits, but none of these homologues have been identified in goats. In this study, we reported the identification of the sheep KRTAP6-5 homologue on goat chromosome 1 and polymerase chain reaction (PCR)-single strand conformation polymorphism analysis in 300 Longdong cashmere goats revealed the existence of 12 variant sequences. Both coding region and 3′UTR of the putative caprine KRTAP6-5 displayed a biggest sequence similarity to ovine KRTAP6-5 gene. This suggested that the gene represents caprine KRTAP6-5 sequences, and these sequences composed 23 genotypes, which was the most polymorphism gene in KRTAPs that have been studied. Among these sequences, 15 nucleotide substitutions and a 24-bp insertion/detection were identified. Variation in goat KRTAP6-5 was associated with variation in mean-fiber diameter, suggesting that KRTAP6-5 is worthy of further study in the context of variation in cashmere traits.